2009
DOI: 10.1021/ja902137z
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum(III) Triflate-Catalyzed Cyclopropanation via Intramolecular Methylene Transfer

Abstract: A new method for cyclopropanation involving intramolecular methylene transfer from an epoxide to an olefin has been developed. This La(OTf)(3)-catalyzed process proceeds with good efficiency and with high stereoselectivity. A range of examples illustrating substrate scope are given along with a mechanistic rationale. Also demonstrated is an asymmetric cyclopropane synthesis that combines enantioselective epoxidation with this methylene-transfer protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…Der Durchbruch gelang vor kurzem Lambert und Hardee,9 die zeigen konnten, dass enantiomerenangereicherte Cyclopropane als einzige Produkte zugänglich sind, wenn man Epoxide als Methylenquelle und La(OTf) 3 als Katalysator verwendet (Schema ). Die entscheidende Entwicklung war die Verwendung einer Lewis‐Säure (0.05 Äquiv.)…”
Section: Methodsunclassified
“…Der Durchbruch gelang vor kurzem Lambert und Hardee,9 die zeigen konnten, dass enantiomerenangereicherte Cyclopropane als einzige Produkte zugänglich sind, wenn man Epoxide als Methylenquelle und La(OTf) 3 als Katalysator verwendet (Schema ). Die entscheidende Entwicklung war die Verwendung einer Lewis‐Säure (0.05 Äquiv.)…”
Section: Methodsunclassified
“…Both the halomethylmetal-mediated reaction (eqn [1]), in which the classical Simmons-Smith reaction [22][23][24] represents the archetypical example, and the transition metal catalyzed decomposition of diazo compounds (for reviews see Refs. 9,19 ½1 ½2 Likewise, alternative routes to the cyclopropane motif, such as the Kulinkovich-de Meijere reaction (eqn [3]), [29][30][31] the recent examples of epoxide methylene-transfer cyclopropanation (eqn [4]) [32][33][34] and nucleophile-promoted intramolecularcycloadditions (eqn [5]) [35][36][37] are excluded from the present summary as these reactions rely on transition metal catalysis. Nowadays, useful asymmetric versions of these reactions exist, either using chiral auxiliaries or employing chiral catalysis.…”
Section: Background To Cyclopropane Synthesismentioning
confidence: 99%
“…During the course of development of a multicatalytic process involving the alcoholysis of epoxyalkenes of the type 58 (Scheme 23), we observed an unusual methylene transfer reaction that produced the cyclopropyl aldehyde 59. [24] Further investigation revealed that (1) the reaction likely proceeded via a Lewis acid induced ring opening of the epoxide by the pendant olefin followed by semi-pinacol-type rearrangement, (2) La(OTf) 3 was the most effective catalyst, and (3) the reaction was completely stereospecific. A number of substrates were productive in this process, which thus offers a useful new approach to prepare remote cyclopropanes with high stereoselectivity.…”
Section: Recent Examples Of Multicatalytic Reactionsmentioning
confidence: 99%